Study on Infestation Level of GIT Parasites of Sheep and Antihelmentic Drug Resistance in Horro District Community Based Sheep Breeding Program - Cherinnat, Tesfaye Mersha (The International Journal of Tropical Veterinary and Biomedical Research, 2024)
Parasites pose a major threat to animal health and welfare globally, with a greater impact in Africa, particularly Ethiopia, due to diverse agro-ecological factors that support various hosts and helminths. This experiment aimed to estimate parasite infestation levels, identify associated risk factors, and detect anthelmintic drug resistance. Fecal sedimentation and flotation techniques were used to identify trematode and nematode eggs, respectively. Two drugs, Albenda-qk 600 mg and Flukash Sheep (Oxyclozanide 340 mg), were tested for resistance, and associated risk factors were analyzed using STATA (version 13). Results showed nematode and trematode prevalence of 66% and 29% pre-treatment, dropping to 7% and 3% post-treatment. Multivariable logistic regression revealed that age and deworming timing were significantly associated with parasite positivity (P 0.05). Despite significant reductions in parasite prevalence post-treatment, some sheep flocks exhibited resistance. To prevent further development of anthelmintic resistance, the following practices are recommended: avoid frequent or unnecessary treatments, apply strategic and integrated drug use, ensure proper dosages, rotate anthelmintic drugs, and regularly perform efficacy tests.